Thyroid doses due to stereotactic radiosurgery of the brain - Sibata, Claudio H. (Radiology and oncology (Ljubljana), 1998)
Background and purpose. Radiosurgery is an irradiation technique in which one high dose fraction or more is applied to a small intracranial volume stereotactically located. The technique is presently in use at the Roswell Park Cancer Institute and it uses 6 non-coplanar arcs, delivered by a 6 MV photon beam from a linear accelerator. One of the issues discussed in the recent BEIR Report V is the radiogenic aspects of solid tumours and the risks related to external radiation. Thyroid carcinoma has been observed to increaseconsistently in a number of irradiated populations. The thyroid gland in children under 15 years of age, has one of the highest risk coefficients ofany organ and is the only tissue with convincing evidence of risk at about 10 cGy. Since children of different ages may also present clinical situations that requires radiosurgery, an investigation was conducted to assess the to the thyroid and other nearby organs. Materials and methods: In-vivo patient measurements were conducted, using TLDs and diodes at the surface of the patient neck corresponding to the thyroid plane as well as with the Alderson phantom for similar geometry and at 0,6 cm of depth in the same plane. Results: The measured thyroid doses in the order of 10 cGy are essentially independent of cone size since the typical doses used in radiosurgery increases considerably as the cone size decreases. Conclusions: A recommendation is made to eliminate or to displace the treatment arc which projection passes through the thyroid plane. This procedure must be adopted for children under 5 years of age and strongly recommended for children up to 15 years of age.
Keywords: Adverse effects; Arteriovenous malformations; Radiation dosage; Radiation effects; Radiosurgery; Thyroid gland; Thyroid neoplasms